Do Chinese mutual fund investors chase returns? - Du, Chen (2012)
On a comprehensive sample of Chinese open-end equity mutual funds from 2005 to 2009, we investigate the non-linear relationship between a fund’s flow and its past performance. We first observe a positive relationship between a fund’s quarterly flow and its prior 12-month return. Next, we find a non-linear relationship between fund flow and past performance using a piecewise regression method. Our result shows that Chinese investor flows are more sensitive to high past fund performance and less sensitive to medium range fund performance. Fund flows do not display statistically significant sensitivity to poor fund performance. After using alternative regression specifications, we confirm the statistical significance of a non-linear flow-performance relationship. In addition, we find that investors’ response to high past performance persists for the first and the second quarter. Lastly, we find that Chinese investors are not sophisticated enough to respond to risk-adjusted performance measures.